PENGARUH PELATIHAN, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CIRAJASA ENGINEERING CONSULTANTS DI JAKARTA - Deni Jauhari; Meiske Claudia; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2021)
This study aims to determine and analyze the effect of training (X1), work motivation (X2) and job satisfaction (X3) as independent variables either partially or simultaneously on employee performance (Y) as the dependent variable at PT. Ciriajasa Engineering Consultants in Jakarta. This research method uses a questionnaire with a total population and the type of research sample is 84 employees of PT. Ciriajasa Engineering Consultants in Jakarta. Measurement of variables using a Likert scale technique with a weight scale from 1 to 5. To find out the correlation between variables X1, X2, X3 to Y using multiple linear regression analysis techniques previously carried out the classical assumption test. The significance test used the F test and the t test with the SPSS program. The results of the study concluded that there was a significant positive effect of each independent variable on the dependent variable. Of the three independent variables, the dominant variable with the highest percentage (31.7%) is work motivation (X2) compared to the other two independent variables. And there is a simultaneous significant effect of three independent variables on employee performance variables.